Potential of Combined Insulin Leaf (Smallanthus sonchifolius) and Noni Fruit (Morinda citrifolia L.) Extracts in Reducing Blood Glucose Level and Spermatogenic Cells Improvement in Diabetic Mice - Sukarjati; Aldi Syahputra (Jurnal Penelitian Pendidikan IPA, 2025)
Elevated blood glucose levels are a hallmark of diabetes mellitus, which can lead to reproductive disorders, particularly affecting spermatogenic cells. This study aimed to evaluate the effectiveness of insulin leaf extract, noni fruit extract, and their combinations in reducing blood glucose levels and their impact on the number of spermatogenic cells in diabetic mice. A total of 36 male mice were divided into 12 treatment groups, including a normal control group, a negative control group (induced with alloxan 120 mg/KgBW), a positive control group (alloxan + metformin), and nine treatment groups with various doses of individual and combined extracts. Blood glucose levels were measured using Accu-Chek, and testicular histology was prepared following laboratory standards. Data were analyzed using the ANOVA test followed by the Duncan post hoc test. Results showed that the combination of insulin leaf extract at 150 mg/KgBW/day and noni fruit extract at 62.5 mg/KgBW/day was the most effective in reducing blood glucose levels. Additionally, the combination of 125 mg/KgBW insulin leaf extract and 50 mg/KgBW noni fruit extract significantly increased the number of spermatogenic cells. Thus, the combination of insulin leaf and noni fruit extracts shows potential as a natural antidiabetic therapy and for restoring spermatogenic cell function in diabetic conditions.